ANALISIS SEBARAN SPASIAL DAN POTENSI PAKAN RUSA TIMOR (Rusa timorensis) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS OELSONBAI DAN SEKITAR NYA KELURAHAN FATUKOA, KECAMATAN MAULAFA, KOTA KUPANG. - Luruk, Wilgis; Riwu Kaho, Ludji Michael; Riwu Kaho, Norman P.L.B. (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This study was conducted to determine the distribution, availability of feed and types of feed, the amount of feeding, and the frequency of feeding the Timor deer in KHDTK Oelsonbai, Kupang City, East Nusa Tenggara Province. This research was conducted at KHDTK Oelsonbai, Fatukoa Village, Maulafa sub-district, Kupang City, East Nusa Tenggara Province. This research was carried out for 2 months, from June to August 2021. This study used the roaming method for the distribution of deer feed, the Vegetation analysis method for the availability of feed and types of feed, and the palatability calculation method to determine the amount of deer feed. The results showed that the distribution of deer feed inside and outside the area was spread over each observation plot. At locations within the area there were 207 points found, while outside the area there were 130 points. the availability of feed inside and outside the area, which is found in several types of vegetation that have the highest INP value, namely lamtoro (Leucaena Leucochephala) and the lowest INP is kesambi (Schleichera oleosa).